Facile synthesis of magnesium-based metal-organic framework with tailored nanostructure for effective volatile organic compounds adsorption. Issue 3 (30th March 2022) - Hu, Zichu; Liu, Hui; Zuo, Ya; Ji, Yufei; Li, Shujing; Zhang, Wanqi; Liu, Zhechen; Chen, Zhangjing; Zhang, Xiaotao; Wang, Ximing
Abstract : A novel Mg(II) metal-organic framework (Mg-MOF) was synthesized based on the ligand of 2, 2'-bipyridine-4, 4'-dicarboxylic acid. Single-crystal X-ray structural analysis confirmed that three-dimensional-nanostructure Mg-MOFs formed a monoclinic system with a channel size of 15.733 Å × 23.736 Å. N2 adsorption isotherm, Fourier transform infrared spectroscopy, thermogravimetric analysis and high-resolution transmission electron microscopy were performed to characterize the thermal stability and purity of the Mg-MOFs. The adsorption studies on four typical volatile organic compounds (VOCs) emitted during wood drying showed that Mg-MOFs have noteworthy adsorption capacities, especially for benzene and β-pinene with adsorptions of 182.26 mg g −1 and 144.42 mg g −1, respectively. In addition, the adsorption of Mg-MOFs mainly occurred via natural adsorption, specifically, multi-layer physical adsorption, accompanied by chemical forces, which occurred in the pores where the VOCs molecules combined with active sites. As an adsorbent, Mg-MOFs exhibit versatile behaviour for toxic gas accumulation.